DAYA BELI MASYARAKAT TERHADAP BAHAN PANGAN POKOK DI KABUPATEN HALMAHERA TENGAH - Muhammad Zais Samiun; Nurdin I Muhammad (Universitas Khairun, 2018)
This study aims to: (1), Knowing the share of expenditure, the progress of prices of staple food and people's income in Central Halmahera Regency, (2), Analyzing the level of people's purchasing power with an indicator of the ratio of income to prices of staple foods in Central Halmahera Regency, and (3), Analyze the level of people's purchasing power with an indicator of the ratio of income to the index of staple food prices in Central Halmahera Regency. The results of the analysis show that the expenditure of community households in Central Halmahera Regency is specifically allocated to fulfill the consumption of fresh rice and fish, followed by consumption of flour, sugar and cooking oil. While the allocation of expenditures for consumption of staple-sourced staple foods includes chicken, milk, eggs and beef is still very low. The price of staple food in Central Halmahera Regency during the observation period of 2009 until 2018 in January - March, tends to increase in the range of 2% - 12%. Whereas on the other hand, the level of income of the community only changes in the range of 5% - 7%, with the highest income enjoyed by employees and entrepreneurs and conversely the lowest income is felt by farmers. The purchasing power of people in Central Halmahera Regency with an indicator of the ratio of income to each of the staple food prices tends to fluctuate but has experienced significant improvements in 2018 compared to 2009, except for the purchasing power measured as equal to beef consumption. The purchasing power equivalent to beef consumption has decreased to 22.32% because the percentage increase in income is less able to compensate for the increase in beef prices. Measured by the income ratio indicator on the basic food price index, people's purchasing power also showed an improvement in 2018 compared to 2009, but that only happened to farmers, construction workers, and civil servants groups I / II. When compared to 2017, public purchasing power in 2018 as a whole decreased by 12.38%. The purchasing power level of people in Central Halmahera Regency from the lowest ranking in sequence is felt by groups of farmers, followed by construction workers, civil servants groups I / II, entrepreneurs and employees.Â